Regional characteristics of chemical constituents in surface snow, Arctic cryosphere - モトヤマ, ヒデアキ; ワタナベ, オキツグ; カミヤマ, コキチ; イガラシ, マコト; アズマ, クミコ; フジイ, ヨシユキ; イイズカ, ヨシノリ; マトバ, スミト; ナリタ, ヒデキ; カメダ, タカオ; Motoyama, Hideaki; Watanabe, Okitsugu; et al. (National Institute of Polar Research, 2001)
P(論文) Surface snow observations were carried out on many glaciers in the Arctic. The observational sites were in Svalbard, Severnaya Zemlya, Greenland and arctic Canada. The seasonal variations of chemical constituents in snowfall remained in the surface snow on the central Greenland ice sheet where the effect of snowmelt was weak. Conversely, the chemical constituents in the snow layer changed with infiltration of melt water on the Svalbard glacier where strong snowmelt occurred, even in high latitudes. But in general, specific regional characteristics remained in all the glaciers. The concentrations of ions in snow were significantly decreased, because of percolation of melt water. But the ratio of NO_3 to Cl still had unique regional characteristic values. departmental bulletin paper